Building a parallel corpus of literary texts featuring onomatopoeias: ONPACOR - Orrequia-Barea, Aroa; Marín-Honor, Cristian (Research in corpus linguistics, 2020)
Onomatopoeias constitute a much neglected subject in linguistics. The rather scarce literature on onomatopoeias is derived from a lack of reliable empirical data on the topic. In order to bridge this gap, we have compiled a parallel corpus of literary texts featuring onomatopoeias: the Onomatopoeia Parallel Corpus (ONPACOR). The corpus consists of onomatopoeias in English, Spanish and French extracted from comics and representative corpora of each language. ONPACOR has been built on the basis of existing translations to the languages of reference. This article describes the methodology used to compile the corpus, as well as the applications that it can have.